OS SENTIDOS DA VIOLÊNCIA SEXUAL CONTRA AS MULHERES EM SITUAÇÃO DE RUA NA REGIÃO LESTE DE SÃO PAULO - SILVA, NATÁLIA MARQUES BAPTISTA (2021)
Among the high rates of women who suffer sexual violence are those on the street. These women need visibility and understanding, aiming at rights and a dignified life. Thus, this dissertation aims to identify the meanings of sexual violence against women on the street. It is a qualitative and descriptive research, carried out with adult women and professionals who meet this demand. The research site was an assistance institution in the eastern region of São Paulo. As a data collection instrument, a focus group and semi-structured interview were conducted. In the first moment, the focus group, of the referred institution, was constituted by 8 participants, being that only 6 had speech. Its configuration was structured in the understanding of what sexual violence is for the group, about the presence of sexual violence in the lives of women and about the protection strategies in these situations. In a second moment, 4 semi-structured interviews were carried out with employees of the multiprofessional team, being a psychologist, a social worker and two socio-educational educators. The interviews were conducted remotely, using a digital application. The collected data were categorized by means of Thematic Analysis, in which initial code generation, definition and naming of themes by patterns of meanings were carried out. From the results achieved, there were two significant meanings to the phenomenon: the actions of the State and the blaming of women. The State did not provide a sufficient response to prevent the occurrence of cases of violence, and this was revealed in: a) professional unpreparedness of the team in dealing with demands for violence; b) the lack of government assistance in the assistance equipment and in the fight against violence against women, arising and permeated by the female blame for the phenomenon, stood out: a) the modes of dress and behavior of women; b) expressions of beliefs about the vulnerability of women arising from the superior physical strength of men, which falls on women to flee and avoid situations conducive to the occurrence; c) the cyclical dynamics of abusive relationships in which women are immersed and allow themselves to continue in these circumstances; d) the abuse of drugs as a support and justification for masculinity; e) the partner's violence being used as a justification and power to act on other violence. d) the abuse of drugs as a support and justification for masculinity; e) the partner's violence being used as a justification and power to act on other violence. Given these data, the meanings presented by the participants are permeated by the production of subjectivity and actions that attribute the responsibility of suffering to women themselves. And, within the limits of being part of the street population, they are relegated solely to individual security and kept under the negligence of the State and society.